1992
DOI: 10.2166/wst.1992.0234
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Separation of Raw and Anaerobically Digested Pig Manure

Abstract: Manure ought to be controlled and handled environmentally soundly. Volume reduction of surplus manure by reverse osmosis (RO) is a viable and economic option in certain areas where another alternative is to reduce the number of animals. This membrane separation project arose out of an urgent need to re-establish an ecological balance between farming and the natural environment without necessarily having to decrease the number of livestock. The suggested technical solutions should not significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…3). For example, Bilstad et al (1992) used RO for nitrogen recovery from digested manure. The process removed 95% of input total nitrogen, which was retained in the liquid fraction (concentrate), and was therefore considered a viable liquid fertilizer (Bilstad et al, 1992).…”
Section: Reverse Osmosismentioning
confidence: 99%
See 1 more Smart Citation
“…3). For example, Bilstad et al (1992) used RO for nitrogen recovery from digested manure. The process removed 95% of input total nitrogen, which was retained in the liquid fraction (concentrate), and was therefore considered a viable liquid fertilizer (Bilstad et al, 1992).…”
Section: Reverse Osmosismentioning
confidence: 99%
“…For example, Bilstad et al (1992) used RO for nitrogen recovery from digested manure. The process removed 95% of input total nitrogen, which was retained in the liquid fraction (concentrate), and was therefore considered a viable liquid fertilizer (Bilstad et al, 1992). Additionally RO is effective at high initial TAN concentrations, as demonstrated by Masse et al (2008) who achieved >99% NH 4 + retention efficiency using AD effluent with high initial TAN levels (10,000 mg L À1 ).…”
Section: Reverse Osmosismentioning
confidence: 99%
“…Membranes are used to treat wastewater and slurry by livestock farming, reduce volume of surplus manure, and produce a concentrated fertilizer [27][28][29][30][31][32][33].…”
Section: Anaerobic Digestion Coupled With Membrane Technologymentioning
confidence: 99%
“…Nowadays, in the agricultural industry, all kinds of membrane processes (microfiltration, ultrafiltration, nanofiltration, and reverse osmose) are implemented . Membranes are used to treat wastewater and slurry by livestock farming, reduce volume of surplus manure, and produce a concentrated fertilizer .…”
Section: Introductionmentioning
confidence: 99%
“…In short-term studies, clean water flux could always be recovered following intensive acidic and alkaline cleaning (Bilstad et al 1992). Atkinson (2005) and Johnson et al (2004), from New Logic Research, reported on the use of Vibrating Shear Enhanced Processing (VSEP) for manure purification.…”
Section: Introductionmentioning
confidence: 99%